A Large Silicon Pool in Small Picophytoplankton - Wei, Yuqiu; Sun, Jun (Frontiers in Microbiology, 2022)
Marine picophytoplankton (<2 µm) play a key role in supporting food web and energy flow in the ocean, and are major contributors to the global marine carbon (C) cycle. In recent years, picophytoplankton have been found to have significant silica (Si) accumulation, a finding which provides a new sight into the interaction of marine C and Si cycles and questions the overwhelming role of large diatoms (>2 µm) in the Si cycle. As picophytoplankton have high cell abundance and wide distribution in the open ocean, exploring their influences on the C and Si cycles as well as other element cycles are becoming new scientific hotspots. However, there are still few studies on the physiology and ecology of picophytoplankton, especially their potential roles in the biogeochemical Si cycle at present. Thus, it is necessary to accurately evaluate and quantify the contributions of picophytoplankton to the C and Si cycles, and to further understand their C and Si sinking mechanisms. In this review, we expect to have a novel understanding of picophytoplankton Si pool and regulation mechanism by conducting targeted studies on these scientific issues. This also provides a premise foundation and theoretical framework for further study of the role of small cells in the global ocean Si cycle and the coupling of C and Si cycles.